2021
DOI: 10.1055/a-1376-6734
|View full text |Cite
|
Sign up to set email alerts
|

Usefulness of New Shear Wave Elastography Technique for Noninvasive Assessment of Liver Fibrosis in Patients with Chronic Hepatitis B: A Prospective Multicenter Study

Abstract: Purpose To explore the usefulness of liver stiffness measurements (LSMs) by sound touch elastography (STE) and sound touch quantification (STQ) in chronic hepatitis B (CHB) patients for staging fibrosis. Methods This prospective multicenter study recruited normal volunteers and CHB patients between May 2018 and October 2019. The volunteers underwent LSM by STE and supersonic shear imaging (SSI) or by STQ and acoustic radiation force impulse imaging (ARFI). CHB patients underwent liver biopsy and LSM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Some studies in the field of medical imaging have reported that magnetic resonance elastography has a higher diagnostic performance than transient elastography (TE) in the staging of liver fibrosis; however, its high cost and low accessibility have limited its clinical utility and patient acceptance (7)(8)(9). Ultrasound elastography has gradually become the primary method for the assessment of liver stiffness due to its convenience, high speed, real-time capability, and low cost (10).…”
Section: Introductionmentioning
confidence: 99%
“…Some studies in the field of medical imaging have reported that magnetic resonance elastography has a higher diagnostic performance than transient elastography (TE) in the staging of liver fibrosis; however, its high cost and low accessibility have limited its clinical utility and patient acceptance (7)(8)(9). Ultrasound elastography has gradually become the primary method for the assessment of liver stiffness due to its convenience, high speed, real-time capability, and low cost (10).…”
Section: Introductionmentioning
confidence: 99%
“…12 The use of elastography techniques is increasing, and various SWE techniques (including those for point and two-dimensional SWE) are available from different vendors. 13,14 Sound touch elastography (STE) is a recently developed ultrasound technology based on the technical principles of two-dimensional SWE. [14][15][16] It employs ultra-wide-beam tracking to create high-quality colorcoded maps of real-time tissue stiffness in a region of interest (ROI), with quantitative analysis.…”
mentioning
confidence: 99%
“…13,14 Sound touch elastography (STE) is a recently developed ultrasound technology based on the technical principles of two-dimensional SWE. [14][15][16] It employs ultra-wide-beam tracking to create high-quality colorcoded maps of real-time tissue stiffness in a region of interest (ROI), with quantitative analysis. [14][15][16] Sound touch quantification (STQ) is based on the technical principles of point SWE.…”
mentioning
confidence: 99%
See 2 more Smart Citations